Joint MMSE Transceiver Designs and Performance Benchmark for CoMP Transmission and Reception. (13th June 2012) - Li, Jialing; Lu, Enoch; Lu, I-Tai
Abstract : Coordinated Multipoint (CoMP) transmission and reception has been suggested as a key enabling technology of future cellular systems. To understand different CoMP configurations and to facilitate the configuration selection (and thus determine channel state information (CSI) feedback and data sharing requirements), performance benchmarks are needed to show what performance gains are possible. A unified approach is also needed to enable the cluster of cooperating cells to systematically take care of the transceiver design. To address these needs, the generalized iterative approach (GIA) is proposed as a unified approach for the minimum mean square error (MMSE) transceiver design of general multiple-transmitter multiple-receiver multiple-input-multiple-output (MIMO) systems subject to general linear power constraints. Moreover, the optimum decoder covariance optimization approach is proposed for downlink systems. Their optimality and relationships are established and shown numerically. Five CoMP configurations (Joint Processing-Equivalent Uplink, Joint Processing-Equivalent Downlink, Joint Processing-Equivalent Single User, Noncoordinated Multipoint, and Coordinated Beamforming) are studied and compared numerically. Physical insights, performance benchmarks, and some guidelines for CoMP configuration selection are presented.